The Integration of the Free Fall Cone Penetrometer (FFCPT) with the Moving Vessel Profiler (MVP) for the Rapid Assessment of Seabed Characteristics - Osler, John; Furlong, Arnold; Christian, Harold; Lamplugh, Mike (The International Hydrographic Review, 2006)
The Free-Fall Cone Penetrometer (FFCPT) is an instrument for the rapid assessment of seabed characteristics, such as grain size and shear strength. The FFCPT also acquires water column sound speed data during its descent to the seabed. The data collection process is very efficient when the FFCPT is deployed by an automated winch system, the Moving Vessel Profiler (MVP). This paper presents engineering, seabed, and SVP data that have been collected from a vessel moving at speeds from 4 to 8 knots.